Genome-Wide Meta-Analysis Identifies Two Novel Risk Loci for Epilepsy - Song, Meng; Liu, Jiewei; Yang, Yongfeng; Lv, Luxian; Li, Wenqiang; Luo, Xiong-Jian (Frontiers in Neuroscience, 2021)
Epilepsy (affects about 70 million people worldwide) is one of the most prevalent brain disorders and imposes a huge economic burden on society. Epilepsy has a strong genetic component. In this study, we perform the largest genome-wide meta-analysis of epilepsy (N=800,869 subjects) by integrating four large-scale genome-wide association studies (GWASs) of epilepsy. We identified three genome-wide significant (GWS) (P<5×10-8) risk loci for epilepsy. the risk loci on 7q21.11 (lead SNP rs11978015, P=9.26×10-9) and 8p23.1 (lead SNP rs28634186, P=4.39×10-8) are newly identified in the present study. Of note, rs11978015 resides in upstream of GRM3, which encodes glutamate metabotropic receptor 3. GRM3 has pivotal roles in neurotransmission and is involved in most aspects of normal brain function. In addition, we also identified three genes (TTC21B, RP11−375N15.2 and TNKS) whose cis-regulated expression level are associated with epilepsy, indicating that risk variants may confer epilepsy risk through regulating the expression of these genes. Our study not only provides new insights into genetic architecture of epilepsy, but also prioritizes potential molecular targets (including GRM3 and TTC21B) for development of new drugs and therapeutics for epilepsy.